Dietary Intake of Children with Type 1 Diabetes in Bahrain: A Case-Control Study - Al-Haddad, Fatima; Musaiger, Abdulrahman; Al-Qallaf, S. Mahmood; Hart, Kathryn (International Journal of Child Health and Nutrition, 2015)
Background & Objectives: Bahrain is reported to rank amongst the top 10 countries for diabetes prevalence worldwide. In particular, growing numbers of children are being diagnosed with Type 1 diabetes mellitus (T1DM).The objective of this study was to describe the dietary intake of Bahraini children with T1DM as compared to a sample of healthy counterparts and to determine whether the nutrient intakes of Bahraini children with T1DM meet the current recommendations. Design & Setting: This was a case-control study. Dietary intake, estimated using a24-hour dietary recall, for the cases was gathered from the Pediatric Endocrine and Diabetes Unit at the Salmaniya Medical Complex and compared to the 24-hour recalls of children without diabetes recruited from Local Health Centers. Patients & Methods: 50 children aged 6-12 years receiving a confirmed diagnosis of T1DM in the years 2009 and 2010 compared with 55 healthy comparators. Results: Children with T1DM consumed significantly more calories than controls (p<0.001) and significantly more protein relative to their RDA (p<0.029). Both groups failed to meet the RDA values for dietary fiber and for Vitamin D. Sodium intakes were in excess of RDA values although no significant difference was observed between groups (p=0.403). Conclusion: The diets of both children with and without T1DM were found to contain excess protein and sodium and inadequate fiber, vitamin D and calcium. Children with T1DM also appeared to consume excess energy and fat. There is a need to endorse existing dietary guidelines for children with T1DM.